Volume 5B: 38th Mechanisms and Robotics Conference 2014
DOI: 10.1115/detc2014-34702
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Bending From Folding in Origami Engineering Using Active Materials

Abstract: Origami engineering — the use of origami principles in engineering applications — provides numerous opportunities to revolutionize the way we design, manufacture, assemble, and package products and devices. By combining origami principles with active materials, we can create reconfigurable products and devices that can fold and unfold on demand. In origami, the folded medium is paper, yet many engineering applications require materials with finite thickness to provide the necessary strength and stiffness to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Several recent publications discuss the difference between bending and folding in shape programming materials. [1][2][3][4][5] Simply stated, folding involves localized deformation whereas bending is global.…”
Section: Figure 2 Differentiates the Subtle Differences Between 'Bendmentioning
confidence: 99%
“…Several recent publications discuss the difference between bending and folding in shape programming materials. [1][2][3][4][5] Simply stated, folding involves localized deformation whereas bending is global.…”
Section: Figure 2 Differentiates the Subtle Differences Between 'Bendmentioning
confidence: 99%
“…The model is made scalable and incorporates thickness (t = 0.01), Young's modulus (E = 10 6 ), Poisson's ratio (ν = 1=4), and density (ρ = 1) of the material (32). A parameter, R FP = 1=10, relates fold line bending to panel bending stiffness and can vary greatly, depending on the materials, the fabrication technique, and the actuation process (33)(34)(35)(36). Using a sensitivity analysis in SI Text, section S3 and Fig.…”
Section: Eigenvalue Analysesmentioning
confidence: 99%
“…4D printed structures, soft robots and actuators and other biomimetic shape morphing systems could also take advantage of field-assisted AM for control [13,[89][90][91]. Other promising research has shown improved mechanical properties such as strength, stiffness, fracture toughness, and damping in composites with the inclusion of non-structural functions in the form of electrical and/or thermal conductivity, sensing and actuation, energy harvesting/storage, self-healing capability, electromagnetic interference (EMI) shielding, recyclability and biodegradability, in order to produce a multifunctional composite structure [136][137][138][139][140][141]. Another important application of polymer composites where electrical conductivity is required is in aircraft structures, where non-conducting structures may be damaged by lightning strikes.…”
Section: Electric Field Assisted Additive Manufacturingmentioning
confidence: 99%